2010
DOI: 10.1128/aem.00055-10
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind Characterization of Non-Genome-Sequenced Bacteria by Mass Spectrometry-Based Proteomics

Abstract: Due to the possibility of a biothreat attack on civilian or military installations, a need exists for technologies that can detect and accurately identify pathogens in a near-real-time approach. One technology potentially capable of meeting these needs is a high-throughput mass spectrometry (MS)-based proteomic approach. This approach utilizes the knowledge of amino acid sequences of peptides derived from the proteolysis of proteins as a basis for reliable bacterial identification. To evaluate this approach, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 30 publications
0
39
0
Order By: Relevance
“…Proteomic analyses by LC-MS have been used in the characterization of bacteria (Castanha,2006;Dworzanski, 2004Dworzanski, , 2006Lambert, 2005;). Given the degree of success for tandem MS-based proteomics in bacterial characterization, a comparative proteomic study was reported about the potential of the outer membrane protein (OMP) and whole cell protein extracts, independently, can distinguish between strains of the same species (Jabbour et al, 2010). Typically, whole cell protein extracts are usually investigated or select portions of the bacterium, such as the outer membrane, are isolated and the proteins extracted there from.…”
Section: Overview Of the Utilization Of Tandem Mass Spectrometry In Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomic analyses by LC-MS have been used in the characterization of bacteria (Castanha,2006;Dworzanski, 2004Dworzanski, , 2006Lambert, 2005;). Given the degree of success for tandem MS-based proteomics in bacterial characterization, a comparative proteomic study was reported about the potential of the outer membrane protein (OMP) and whole cell protein extracts, independently, can distinguish between strains of the same species (Jabbour et al, 2010). Typically, whole cell protein extracts are usually investigated or select portions of the bacterium, such as the outer membrane, are isolated and the proteins extracted there from.…”
Section: Overview Of the Utilization Of Tandem Mass Spectrometry In Bmentioning
confidence: 99%
“…Alternatively, high-throughput tandem mass spectrometry-based proteomics was applied as a means for characterizing cellular proteins and producing amino acid sequence information for peptides derived from these proteins for E. coli and Y. pestis. Whole cell protein and cell membrane OMP extracts were compared and contrasted with the in-house BACid bioinformatics modeling tools for species and strain level discrimination (Jabbour, 2010).…”
Section: Outer Membrane Proteins For Bacterial Strains Differentiationmentioning
confidence: 99%
“…Strain level identification was obtained for S. aureus ATCC 3359, a strain whose genome has yet to be sequenced. All of the unsequenced bacteria in the blind sample were correctly speciated, further demonstrating that comparing the experimentally obtained peptides to the virtual digests in the proteome could yield statistically significant identification (Jabbour et al, 2010). It is apparent that the utility and precision of MADLI-TOF MS, MALDI-TOF-TOF MS/MS and LC-ESI-MS-MS are all reliant on the development and maintenance of accurate and representative databases.…”
Section: Liquid Chromatography Electrospray Tandem Mass Spectrometry mentioning
confidence: 99%
“…It is also necessary to have some prior knowledge of the gene of interest in order to create operational primers. Additionally, effective primer selection requires there be two conserved regions for genetic recognition and amplification, thereby limiting the number of useful genes (Jabbour et al, 2010;Fox et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Using this LC-MS/MS method, proteins of pure cultures of a microorganism are digested with trypsin, generating peptides of which the amino acid sequence is determined based on their measured masses, the masses of fragmentation product ions and their comparison with in silico trypsin digests and corresponding predicted fragments of a protein database. From these peptide sequences, not only proteins of interest can be identified, also the micro organism itself can be specified to, at least, species level [16,17]. Recent developments in proteomic analysis using LC-MS/MS reduced the time to result, making it possible to analyze a sample within 6 h [18].…”
Section: Research Articlementioning
confidence: 99%